Trends and Patterns in Political Communication Research: A Bibliometric Analysis of Scopus-Indexed Articles - Judijanto, Loso; Haryadi, Haryadi (The Eastasouth Journal of Social Science and Humanities, 2025)
This study delineates the global landscape of sustainopreneurship research from 2000 to 2025 by bibliometric analysis utilizing the Scopus and Web of Science databases. We used VOSviewer and Biblioshiny to look over 320 texts to find the intellectual, social, and conceptual frameworks of the topic. The results show that sustainopreneurship has grown into a field that combines sustainability, innovation, and entrepreneurship. Major research clusters focus on subjects including social innovation, sustainable development, the circular economy, and entrepreneurship education. Newer areas include digital entrepreneurship and using AI for sustainability. Collaboration networks show that India, the United States, China, Germany, and Spain are the biggest donors. This is made possible by strong institutional links across countries in Asia, Europe, and Africa. The research advances theoretical frameworks by establishing sustainopreneurship as a hybrid construct that integrates corporate innovation with sustainable development. It tells policymakers and educators about the latest trends in global collaboration and the most important areas for sustainable entrepreneurship education and investment.